Seculariseren de achterbannen van de confessionele partijen mee? - Ruben Konig (Religie & Samenleving)
Over de last three decades, Dutch society has shown a trend towards increasing individualization. Thus the question arises, whether this is also true for the constituency of Dutch political parties. A question that is especially interesting with respect to religious political parties, because secularization is an integral part of individualization. With joint correspondence analysis, based on seven national surveys between 1979 and 2012, we could show that the constituencies of the religious political parties have all gone through a process of individualization, and thus secularization. This process has made the Christian Democrats (CDA) lose their Christian appeal among voters to a large extent, but the smaller Christian parties (Christen Unie and SGP) still have a Christian backing.